The design and execution of mentorship programmes for black-owned small enterprises in the Northern Cape - Titus, Xolile (University of the Free State, 2018)
Abstract not available
Dissertation (M.Dev.St. (Centre for Development Support))--University of the Free State, 2018
Keywords: Small businesses; Mentorship programmes; Black-owned enterprises; Small enterprises; Mentorship